Complete genome sequence of the bile-resistant pigment-producing anaerobe Alistipes finegoldii type strain (AHN2437T). Issue 1 (January 2013) - Mavromatis, Konstantinos; Stackebrandt, Erko; Munk, Christine; Lapidus, Alla; Nolan, Matt; Lucas, Susan; Hammon, Nancy; Deshpande, Shweta; Cheng, Jan-Fang; Tapia, Roxanne; Goodwin, Lynne; Pitluck, Sam; et al.
Abstract Alistipes finegoldii Rautioet al. 2003 is one of five species ofAlistipes with a validly published name: familyRikenellaceae, orderBacteroidetes, classBacteroidia, phylumBacteroidetes . This rod-shaped and strictly anaerobic organism has been isolated mostly from human tissues. Here we describe the features of the type strain of this species, together with the complete genome sequence, and annotation.A. finegoldii is the first member of the genusAlistipes for which the complete genome sequence of its type strain is now available. The 3, 734, 239 bp long single replicon genome with its 3, 302 protein-coding and 68 RNA genes is part of theG enomic E ncyclopedia of B acteria and A rchaea project.